Psychology of financial planning the practitioner's guide to money and behavior - Klontz, Brad; Chaffin, Charles R.; Klontz, Ted (Ascent Audio, 2022)
In Psychology of Financial Planning: The Practitioner's Guide to Money and Behavior, distinguished authors Drs. Brad Klontz, CFP, Charles Chaffin, and Ted Klontz deliver a comprehensive overview of the psychological factors that impact the financial planning client. Designed for both professional and academic audiences, Psychology of Financial PLanning is written for those with thirty years in practice as well as those just beginning their journey. With a focus on how psychology can be applied to real-world financial planning scenarios, Psychology of Financial Planning provides a much-needed toolbox for practicing financial planners who know that understanding their client's psychology is critical to their ability to be effective. The Psychology of Financial Planning is also a much-needed resource for academic institutions who now need to educate their students in the CFP Board's newest category of learning objectives: psychology of financial planning.
Online resource; title from title details screen (O'Reilly, viewed November 22, 2022)
Keywords: Finance, Personal -- Psychological aspects; Financial security; Sécurité financière; Finance, Personal; Psychological aspects; Audiobooks; Livres audio